2022
DOI: 10.1590/0100-3984.2022.0020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound reference values for peripheral nerve cross-sectional areas and indices in a sample of healthy individuals in Brazil

Abstract: Objective: To establish peripheral nerve cross-sectional area (CSA) reference values (absolute values, measures of asymmetry, and measures of focality) for healthy individuals in Brazil. Materials and Methods: Sixty-six healthy volunteers underwent high-resolution ultrasound of the peripheral nerves. We obtained CSA measurements for three peripheral nerves, at specific locations: the median nerve, in the carpal tunnel (MT); the ulnar nerve, at the cubital tunnel site (UT) and at the pre-tunnel site (UPT); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Although in many cases magnetic resonance imaging (MRI) continues to be the gold standard for nerve imaging, especially for the identification of deep nerves, ultrasound has become an essential imaging technique because of its ability to offer dynamic information, its more widespread availability, and its lower cost (in comparison with MRI) (1) . I totally agree with Voltan et al (2) , as published in the previous issue of Radiologia Brasileira, that high-resolution ultrasound provides information complementary to that obtained by electroneuromyography, especially on the morphology of nerve fascicles and the vascularization of peripheral nerves. Those authors also stated that, as well as being noninvasive and rapidly executed, high-resolution ultrasound can be used in order to assess neural dimensions, locate compression zones within fibrous tunnels, identify tumors, and diagnose traumatic pathologies (2) .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Although in many cases magnetic resonance imaging (MRI) continues to be the gold standard for nerve imaging, especially for the identification of deep nerves, ultrasound has become an essential imaging technique because of its ability to offer dynamic information, its more widespread availability, and its lower cost (in comparison with MRI) (1) . I totally agree with Voltan et al (2) , as published in the previous issue of Radiologia Brasileira, that high-resolution ultrasound provides information complementary to that obtained by electroneuromyography, especially on the morphology of nerve fascicles and the vascularization of peripheral nerves. Those authors also stated that, as well as being noninvasive and rapidly executed, high-resolution ultrasound can be used in order to assess neural dimensions, locate compression zones within fibrous tunnels, identify tumors, and diagnose traumatic pathologies (2) .…”
supporting
confidence: 90%
“…I totally agree with Voltan et al (2) , as published in the previous issue of Radiologia Brasileira, that high-resolution ultrasound provides information complementary to that obtained by electroneuromyography, especially on the morphology of nerve fascicles and the vascularization of peripheral nerves. Those authors also stated that, as well as being noninvasive and rapidly executed, high-resolution ultrasound can be used in order to assess neural dimensions, locate compression zones within fibrous tunnels, identify tumors, and diagnose traumatic pathologies (2) . Given the lack of data on this topic in the literature, it is important that the authors demonstrated that the peripheral nerve cross-sectional areas were lower in a sample of the Brazilian population than in most of the other samples described in the literature.…”
supporting
confidence: 90%
“…For comparison of the values obtained for the patients, we considered the values established by Voltan et al ( 54 ) as normality standards (healthy individuals—none of whom had any known contact with leprosy) for CSAs in the Brazilian population.…”
Section: Resultsmentioning
confidence: 99%
“…The nerves were considered to be enlarged when their CSA was greater than the mean ± 2 SD of the normal values established in the study by Voltan et al ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation